Effectiveness Of The Demonstration Method And Discovery Method On Mother's Knowledge About The Completeness Of Basic Immunization In Infants At The Uptd Puskesmas Inpatient Warunggunung Lebak- Banten - Dewi Agustin Eka Rahmawati; Nur Anita (Lembaga Pengembangan Kinerja Dosen, 2023)
Child health issues are one of the government's priorities in creating a quality generation. One effort for this purpose, all children under five are immunized. The challenge of implementing the immunization program that causes the target of immunization coverage not to be achieved is the lack of knowledge. In an effort to increase knowledge, the role of health workers, especially midwives, is to provide information through health education using both the demonstration method and the discovery learning method. This study aims to determine the effectiveness of the demonstration method and the discovery method on mother's knowledge about the completeness of basic immunization in infants at the UPTD Inpatient Health Center Warunggunung - Lebak Banten 2023. This study used a pre-experimental design with one group pretest-posttest design. One-group pre-post test design to obtain knowledge data before and after the intervention. The number of samples in this study were 66 mothers who had babies who met the inclusion criteria. The instrument used for data collection used a questionnaire and then the data were analyzed using a paired test and an independent sample T test. The results of the research produced in this study were that the mother's knowledge before the intervention was included as lacking and after being given the intervention with demonstration and discovery was sufficient. There is an influence of health education demonstration and discovery methods on mother's knowledge about completeness of basic immunization (p value 0.000). There is no difference in the effectiveness of the demonstration method and the discovery method on mother's knowledge about the completeness of basic immunization in infants with a p value of 0.068.